Failed OECS political union initiative : lessons for regional integration in the Anglophone Caribbean - Lewis, Patsy (1999)
Locates the attempt, between 1986 and 1992, to forge a political union, first among the member states of the OECS, and subsequently among the Windward Islands, both within the context of theoretical debates on federal and functional forms of integration, as well the experience of the failed West Indies Federation. Seeks to identify the factors contributing to interest in such a political union and why it ultimately failed. Argues that political union among some, if not all members of the Anglophone Caribbean, remains relevant as long as there continues to exist seemingly 'non-viable' units locked into dependent relationships with the US and Europe.